2012
DOI: 10.5771/0943-7444-2012-4-292
|View full text |Cite
|
Sign up to set email alerts
|

Including Authorial Stance in the Indexing of Scientific Documents

Abstract: Information Science & Communication Studies at Grenoble3University. She is a member of Gresec (research group in Information and Communication Studies, Grenoble, Stendhal University). Her research interests revolve mainly around information retrieval and indexing of scientific and professional discourse.Céline Paganelli is Associate Professor in Information & Communication Studies at Montpellier 3 University. She is a member of Gresec (research group in Information and Communication Studies, Grenoble, Stendhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The BCC has an entire schedule of adjectival qualities that might be applied in this synthetic approach (Other general classifications that are enumerative in approach may have a less extensive list of stand-alone qualities to employ here.) Works about art might be distinguished as to whether they are works of connoisseurship, criticism, and so on (see Clavier and Paganelli 2011). Different aesthetic theories would be captured above under theory.…”
Section: Aesthetic Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCC has an entire schedule of adjectival qualities that might be applied in this synthetic approach (Other general classifications that are enumerative in approach may have a less extensive list of stand-alone qualities to employ here.) Works about art might be distinguished as to whether they are works of connoisseurship, criticism, and so on (see Clavier and Paganelli 2011). Different aesthetic theories would be captured above under theory.…”
Section: Aesthetic Outlookmentioning
confidence: 99%
“…Information scientists have long recognized the potential benefits of classifying authorial perspective. In particular, this would help users evaluate the potential relevance of works (Clavier and Paganelli 2011). And of course it would alert users to potential biases in the text (Gutierrez and Martinez-Avila 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Feinberg suggested that classificationists in particular should confess their perspective, but we might well propose that authors also could express this. Clavier and Paganelli (2012) argue that we should classify works by stance: criticism, agreement, consensus, and so on. A key challenge for the information scientist is that there are imperfect correlations across these dimensions: not all who apply feminist theory are female, and feminist theory is applied outside of gender studies.…”
Section: Purposementioning
confidence: 99%
“…What about humanities scholarship? Clavier and Paganelli (2012) argue that we should classify all works by authorial stance: criticism, agreement, consensus, and so on. It would seem that it would be useful to distinguish different texts about art:…”
Section: Perspectivementioning
confidence: 99%